Survival Rates Of Patients With Oral Cancer In Pakistan , Analysing The Related Risk Factors, Social Determinants, Preventive Measures And Treatment Modalities. A Retrospective Study - Zahid, Anita; Shafiq, Seema; Khan, Aamna Batool; Yousaf, Saba; Anis, Mehak; Sahito, Muhammad Amin (Journal of Neonatal Surgery, 2025)
Background : Oral cancer begins as a persistent growth or sore in the mouth. Oral cancer, which includes malignancies of the lips, tongue, cheeks, floor of mouth, hard and soft palates, and pharynx (throat), can be fatal if not detected and treated promptly. It is a significant public health issue globally, but there is a notable disparity in its prevalence. In 2018, an estimated 177,384 deaths and 354,864 new cases of lip and oral cavity cancers were reported, with Asia alone accounting for over 70% of the deaths. According to the research, males are twice as likely as women to acquire oral cancer, with men over the age of 50 having the highest risk. Smoking is one of several risk factors for developing mouth cancer.Cigarette, cigar, and pipe smokers are six times more likely than nonsmokers to get mouth cancer. Users of smokeless tobacco, such as dip, snuff, or chewing tobacco, are 50 times more likely to acquire cheek, gum, and lip cancer. In our country, paan, chalia, and gutka are the leading causes of monthly cancer. Oral malignancies are approximately six times more likely in drinkers than in nondrinkers. Human Papillomavirus (HPV) strains are etiologic risk factors for oropharyngeal squamous cell carcinoma. Socioeconomic status is another risk factor contributing to oral cancers in developing countries like Pakistan and India. Objective: To know the Survival rates of patients with oral cancer in Pakistan , analysing the related risk factors, social determinants, preventive measures and treatment modalities Method:.This is a retrospective, observational institutional based that was carried out at the oral and maxillofacial surgery JPMC Abbasi Shaheed Hospital Karachi 3 months after the approval of the synopsis. Results:Oral cancers were studied separately in three groups: OC, lip, and salivary glands. OC tumours were more frequent (47%). The majority of all cancer patients were men (59%) and in the 41-64 age group (43%). The mean age of the patients was 61.2 (SD 15, median 64, range 14-103), 58.7 (SD 14, median 62, range 27-87), and 51.5 (SD 17, median 52, range 6-85) for OC, lip, and salivary gland cancers, respectively (P < 0.001). A clear gender and age difference emerged between patients with these tumours (P < 0.001). Males dominated, especially in lip cancers (85%), and the majority of the patients in all these three groups were over 40 . Further analyses showed no gender difference by age within these three tumor sites.Tongue cancers were the most prevalent OC type (50%). Conclusion: OC tumours are the most frequent.The majority of all cancer patients are men and in the 41-64 age group. The overall five-year survival rate of patients with OC cancer is 30%.Survival is negatively related to stage of tumour at the time of diagnosis. The overall five-year survival rate of patients with lip cancer is 62%. The survival was higher in patients diagnosed at earlier tumour stages than in those diagnosed at advanced stages.